Quantifying dorsal Hippocampal CA-1 pyramidal cells in rats: rules to light microscope based estimation - Azzubaidi, Marwan Saad; Saxena, Anil Kumar; A.Talib, Norlelawati (Universiti Putra Malaysia, 2013)
The brain’s hippocampus which controls memory and learning is the first structure affected by neurodegeneration in Alzheimer’s disease (AD). The number of viable hippocampal CA1 pyramidal cells (HCA1PC) is significantly decreased in AD and in rats with 2 vessel occlusion (2VO), an established animal model for AD. The variability in three dimensional arrangements of HCA1PC between dorsal and ventral portions of the hippocampus made the calculation of HCA1PC subject to debate. As errors and biases in the counting technique can be overcome by implementing a standardized procedure, the current study proposed a procedure for quantification of the viable HCA1PC by standardizing the method of tissue sectioning. Sixteen rats were divided into 2VO and sham control with eight animals per group. Coronal sections were made based on the anatomical landmarks of medial section of rat’s cerebral hemispheres. Under light microscope with cresyl violet staining, the number of viable HCA1PC in 1 mm horizontal distance of dorsal hippocampus, 3 mm caudal to the fornix, was calculated twice and found to be significantly higher in sham control than 2VO group (p<0.01) with standard error of mean of 4.98 and 17.26 respectively. This indicates successful establishment of the standardized technique with feasible reproducibility.